Chronic non-communicable diseases: Hainan prospective cohort study. Issue 11 (18th November 2022) - Gu, Xingbo; Lin, Liuting; Zhao, Chanjuan; Wu, Ling; Liu, Yumei; He, Limin; Lin, Guotian; Lin, Yingzi; Zhang, Fan
Abstract : Purpose: The Hainan Cohort was established to investigate the incidence, morbidity and mortality of non-communicable diseases and their risk factors in the community population. Participants: The baseline investigation of the Hainan Cohort study was initiated in five main areas of Hainan, China, from June 2018 to October 2020. A multistage cluster random-sampling method was used to obtain samples from the general population. Baseline assessments included a questionnaire survey, physical examination, blood and urine sample collection, and laboratory measurements, and outdoor environmental data were obtained. Findings to data: A total of 14 443 participants aged 35–74 years were recruited at baseline, with a participation rate of 90.1%. The mean age of the participants was 48.8 years; 51.8% were men, and 83.7% had a secondary school or higher education. The crude prevalence of diabetes, coronary heart disease, stroke, hypertension, hyperuricaemia, chronic bronchitis, pulmonary tuberculosis, asthma, cancer, chronic hepatitis and metabolic syndrome were 8.6%, 9.2%, 2.0%, 37.1%, 7.1%, 2.3%, 1.4%, 2.1%, 4.1%, 2.2% and 14.5%, respectively. Future plans: The Hainan Cohort is a dynamic cohort with no end date. All participants will be monitored annually for cause-specific mortality and morbidity until death. Long-term follow-up will be conducted every 5 years. The baseline population is considered to expand in the next wave of follow-up, depending on the availability of funding support.